Embryonic Thermal Manipulation and in ovo Gamma-Aminobutyric Acid Supplementation Regulating the Chick Weight and Stress-Related Genes at Hatch - Goel, Akshat; Ncho, Chris Major; Jeong, Chae-Mi; Choi, Yang-Ho (Frontiers in Veterinary Science, 2022)
Chickens are exposed to numerous types of stress from hatching to shipping, influencing poultry production. Embryonic manipulation may develop resistance against several stressors. This study investigates the effects of thermoneutral temperature (T0; 37.8°C) with no injection (N0) (T0N0), T0 with 0.6 ml of 10% in ovo gamma-aminobutyric acid (GABA) supplementation (N1) at 17.5th embryonic day (ED) (T0N1), thermal manipulation (T1) at 39.6°C from the 10th to 18th ED (6 h/day) with N0 (T1N0), and T1 with N1 (T1N1) on hatchability parameters and hepatic expression of stress-related genes in day-old Arbor Acres chicks. The parameters determined were hatchability, body weight (BW), organ weight, hepatic malondialdehyde (MDA), and antioxidant-related gene expression. Percent hatchability was calculated on a fertile egg basis. Growth performance was analyzed using each chick as an experimental unit. Eight birds per group were used for organ weight. Two-way ANOVA was used taking temperature and GABA as the main effect for growth performance and gene expression studies. Analysis was performed using an IBM SPSS statistics software package 25.0 (IBM software, Chicago, IL, USA). Hatchability was similar in all the groups and was slightly lower in the T1N1. Higher BW was recorded in both T1 and N1. Intestinal weight and MDA were higher in NT-OVOG against T0N0 and T1N1, respectively. The expression of HSP70, HSP90, NOX1, and NOX4 genes was higher and SOD and CAT genes were lower in the T1 group. The present results show that T1 and N1 independently improve the BW of broiler chicks at hatch, but T1 strongly regulates stress-related gene expression and suggests that both T1 and N1 during incubation can improve performance and alleviate stress after hatch.